Changing Returns to Education in Portugal during the 1980s and Early 1990s: OLS and quantile regression estimators - Joop Hartog; Pedro T. Pereira; José A.C. Vieira (Tinbergen Institute, 1999)
This paper examines the evolution of the returns to education in Portugal over the 1980s andearly 1990s. The main findings indicate that the returns to education have increased,particularly after joining the European Union in 1986. Since this occurred along with anincrease in the level of education within the labour force, the process is most likely demanddriven. The results also indicate that modelling on average (i.e. OLS) misses importantfeatures of the wage structure. Quantile regression (QR) analysis reveals that the effect ofeducation is not constant across the conditional wage distribution. They are higher for thoseat higher quantiles in the conditional wage distribution. Wage inequality expanded inPortugal over the 1980s and the returns to education had an important role in this process.
Keywords: 330; Bildungsökonomik; Bildungsertrag; Schätzung; Theorie; Portugal